Association between livestock exposures and human tuberculosis in Wardha, Central India: An exploratory case-control study - Hindol Maity; Pratibha Narang; Shilpa Moon; Rahul Narang; Abhishek Raut; Maroudam Veerasami; Sreenidhi Srinivasan; Premanshu Dandapat; Vivek Kapur; Mohan Papanna (PLoS ONE, 2026)
Background India faces the highest burden of human and bovine tuberculosis (TB) globally. Despite this, the association between human TB and livestock exposure remains poorly understood. This exploratory study aimed to evaluate the association between human TB and livestock contact in Wardha district, Maharashtra, India. Methods A case-control study was conducted from 01/03/2021 to 31/03/2022. Cases were microbiologically confirmed TB patients in HDSS villages, while controls were asymptomatic individuals from the same villages without TB history. Livestock in these households (HHs) were screened for TB using Interferon-Gamma-Release-Assay (IGRA), Single Cervical-Test (SCT), and Comparative-Cervical-test (CCT). Additionally, community-pooled milk samples were cultured for Mycobacterium tuberculosis complex. Fisher’s exact test was used to calculate crude odds ratios and logistic regression for adjusted odds ratios (AOR) with 95% confidence intervals (CI). A post hoc exploratory analysis to understand the relationship between effect size and sample size requirements was done. Results The study included 52 cases and 205 controls, with a median age of 36.5 years (56% men) and 38.5 years (74% men), respectively. Analysis revealed that ownership of livestock and direct contact with cattle did not significantly alter TB risk in humans. Contact with goats showed a marginal association with human TB (AOR: 3.0; 95% CI: 1.0–9.2; p = 0.05). Of 290 livestock screened for TB, none tested positive by confirmatory tests (CCT/IGRA). While 10.2% of cattle showed reactivity to the SIT, this likely represents cross-reactivity with environmental mycobacteria. All bulk milk samples ( n = 201) tested negative for MTBC. Post-hoc power analysis revealed that the study had limited statistical power (41%) to detect the observed association with goat contact. Conclusion This study found no evidence of bovine TB in livestock or milk samples. While contact with goats showed a marginal association requiring further investigation, livestock ownership and raw milk consumption did not show strong associations with human TB. The absence of confirmed TB in animals suggests zoonotic transmission is not a significant contributor to human TB in this setting. The results highlight the need for larger, regionally diverse studies to better understand livestock-associated TB risk factors in India.